Using imagery to predict self-confidence and anxiety in young elite athletes - Strachan, L.; Munroe-Chandler, K. (Journal of Imagery Research in Sport and Physical Activity, 2006)
As elite sport participation by children increases, it is important to study the psychological development of these athletes, specifically the management of self-confidence and anxiety. Imagery is one strategy that may be used by young athletes in controlling cognitions in competition (Weiss, 1991). Although research has been conducted examining imagery use by adult athletes (Hall, 2001), there have been fewer studies investigating how imagery is related to self-confidence and anxiety in young elite athletes (c.f., Vadocz et al., 1997) hence the purpose of the current study. Female participants were recruited from baton twirling competitions in Canada and the USA. Seventy-six athletes were divided into two age cohorts: 7-11 and 12-15 years. A modified version of the Sport Imagery Questionnaire (SIQ; Hall et al., 1998) and the Competitive State Anxiety Inventory 2 for Children (CSAI-2C; Stadulis et al., 2002) were given to each participant. Results indicated that developmental differences might exist between the two age cohorts in imagery use, self-confidence, and anxiety.